Determinação da época adequada de colheita do feijão (Phaseolus vulgaris L) com base na qualidade fisiológica das sementes - da Silva, Claudio Manuel; Vieira , Clibas; Sediyama, Carlos S (Revista Ceres, 2025)
Experiments were carried out in Viçosa to determine the optimal harvest time for the bean (Phaseolus wvulgaris L.) variety ’Rico 23’. Physiological quality of the seeds was used as the basis for this determination.